Program Religius Mahasiswi KKN STIBA Makassar sebagai Upaya Menjaga Eksistensi Muslimah di Kalimantan Barat - Rosmita Rosmita; Fauziah Ramdani (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The purpose of the Real Work Lecture (KKN) stiba Makassar Batch IV is to improve the ability to read the Qur'an and Islamic insight of Kubu Raya Muslimah. The method of implementation of the service program begins by mapping the problems and needs of the community using SOAR Analysis. After the analysis is done, it is prepared a work program that is appropriate and needed by the community. Successful work programs include: Silaturahim Muslimah, Mahir Bahasa Arab, Tausiah Qur'ani, Daurah 7 Days memorization Juz 30, Daurah Ramadan Muslimah, Social Service, Tarbiah and Tahsin Pekanan and Da'wah Social Media. All these programs managed to run well, community enthusiasm increased and the understanding of community religion is also getting better, and has shown results in accordance with the goals of the KKN that has been proclaimed, maintaining the existence of Muslim women.